Anxiety and Scholastic Achievement of Moroccan EFL College Learners - Akhajam Saad Eddine (JEELS (Journal of English Education and Linguistics Studies), 2016)
The main purpose of this study is to investigate the relationship between anxiety and scholastic achievement among students of English department at the faculty of Arts and Humanities of Meknes, Morocco. This study focuses on the level of anxiety among English department students and how they can reduce anxiety inside and outside the classroom in a foreign language speaking environment without instructors‟ intervention. This quantitative research used two instruments; Cattle's anxiety questionnaire to test the level of anxiety and achievement test to measure their scholastic achievement. The results revealed that girls are more anxious than boys, boys achieve higher marks in scholastic achievement, and there is no relationship between anxiety and scholastic achievement.